SKRINING FITOKIMIA DAN POTENSI AKTIVITAS ANTIOKSIDAN EKSTRAK METANOL DAUN SINGKIL (Premna corymbose Roxb & Willd.) DENGAN METODE DPPH (1,1-diphenyl-2-picrylhydrazil ): A MINI REVIEW - Dewi, Camelia Eugenia; Saleh, Chairul; Daniel, Daniel; Magdaleni, Agustina R. (PROSIDING SEMINAR KIMIA, 2024)
Singkil leaves (Premna corymbose Roxb & Willd.) are a plant that is widely found in Kalimantan, and usually grows in the yard of houses or plantations. A research on phytochemicals screening and antioxidant activity test of singkil leaves (Premna corymbose Roxb & Willd.) using DPPH (1,1- diphenyl-2-picrylhydrazyl) method had been conducted. Test for alkaloids, triterpenoids/steroids, phenolic, flavonoids, saponins, and quinone were included in phytochemical screening. The results of the literature show that the methanol extract exhibits antioxidant activity in the strong category, which has an IC50 value of 20.66 μg/ml. Methanol extract of singkil leaves (Premna corymbose Roxb & Willd.) has potential as an antioxidant. Keywords: Singkil leaves (Premna cordifolia Roxb.), phytochemical screening, antioxidant, DPPH